(untitled) (International Journal of Food and Nutritional Sciences, 2022)
BACKGROUND:Osteoarthritis is one among the most common condition which occurs in geriatric population which is one of the major causes for the decline in physical activities. This degenerative arthritis damages the articular cartilages that protect the articular surface over a period of time.Osteoarthritis predominantly affects the sensory components of a joint in which balance sense is very much affected in comparison with a normal person of same age group. Objective of the study was to find out the effect of kinesthetic balance exercises along with core stabilization exercises on knee pain and balance among elderly people with OA knee. METHOD: 10 elderly people with OA knee patients were selected. The outcomes were measured by using NPRS for pain and Y-Balance test for balance. The 10 subjects were treated with kinesthetic balance exercise along with core stabilization exercise, the total treatment duration of 12 weeks. RESULTS:These results demonstrate the significant improvement in reducing knee pain and improvement in balance among elderly people with OA knee. CONCLUSION:The kinesthetic balance exercises in combination with core stabilization exercises reduce the knee pain and improve the balance in elderly population with knee osteoarthritis